At the Heart of the Mothercrystal: Final Fantasy XIV’s Approach to Localization and Lore as a Virtual Contact Zone - Vichot, Rhea (Loading)

(untitled) (Canadian Game Studies Association, 2024)
Virtual worlds by nature of their persistence and ability to have multiple simultaneous users in the same space can act as contact zones, defined by Mary Louse Pratt as a "social space where disparate cultures meet, clash, and grapple with each other, often in highly asymmetrical relations of domination and subordination," (1991, p. 34). One affordance of virtual worlds in constructing the contact zone is the ability for the developer to use localization to bridge language gaps between a user and the virtual world and, to some extent, between players who have a shared understanding of the virtual world. This understanding extends to the properties of objects and locations and any narrative lore or background in the world. However, localization can be a double-edged sword, with choices in translation and localization leading to confusion among virtual world users and conflict between users and developers.Language impacts two aspects of the virtual contact zone. For one, players communicate using languages they are proficient in, using whatever affordances are available in the interface and paratextual platforms, such as the official forums and social mediaplatforms like Reddit and Tumblr. For another, the world itself is awash in language. That text manifests itself in gameplay elements from user abilities and item names to more narrative elements such as character names, dialogue, and written story and worldbuilding elements. These textual and narrative components, called "lore," are essential in contextualizing virtual spaces. Lore helps build the virtual world beyond the actual mechanics and interactions within a virtual space. Lore gives users a sense of not just place but of geography, not just time, but of history, and not just context for players but their place within the story of the virtual world. Lore offers players motivation for playing in addition to traditional gameplay motivators such as exploration, achieving, socializing, and defeating enemies or other players (Yee, 2006; Bartle, 1996) to interact with the world.This paper focuses on the case of Final Fantasy XIV: A Realm Reborn (FFXIV), an MMORPG initially released in 2013, its production, approaches to localization,and how it contributes to building a "virtual contact zone." In looking at specific instances where controversies in translation and localization led to confusion and conflict among the participants and developers of the game, this case study illustrates the role of localization in games beyond translation and acculturation. Localization not only serves as the linguistic bridge among members of the contact zone but, in the case of online games where world-building and narrative are important aspects for immersion and play, creates shared experiences and understandings of that virtual world among all members of the virtual contact zone.